2016
DOI: 10.1016/j.brainres.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Sustained alterations in neuroimmune gene expression after daily, but not intermittent, alcohol exposure

Abstract: Acute ethanol intoxication is associated with Rapid Alterations in Neuroimmune Gene expression (RANGE), including increased Interleukin (IL)-6 and nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα), and suppressed IL-1β and Tumor necrosis factor (TNF) α, yet little is known about adaptations in cytokines across the first few ethanol exposures. Thus, the present studies examined central cytokines during intoxication (3 h post-ethanol) following 2, 4 or 6 intragastric etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…resulted in sustained IL-6 and IκBα expression in the hippocampus after as many as 6 once-daily exposures, whereas the amygdala and BNST showed signs of habituation. These alterations were independent of blood ethanol concentrations observed, and were seen after repeated daily administration as opposed to every-other-day exposure to the same dose, which did not produce changes in these brain regions, showing the schedule and site specificity of the RANGE effects (Gano et al, 2016). Interestingly, recent work indicated that adolescents display similar patterns of cytokine expression after acute ethanol challenge, though the effects were severely blunted relative to young adults in most structures (Doremus-Fitzwater et al, 2015).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…resulted in sustained IL-6 and IκBα expression in the hippocampus after as many as 6 once-daily exposures, whereas the amygdala and BNST showed signs of habituation. These alterations were independent of blood ethanol concentrations observed, and were seen after repeated daily administration as opposed to every-other-day exposure to the same dose, which did not produce changes in these brain regions, showing the schedule and site specificity of the RANGE effects (Gano et al, 2016). Interestingly, recent work indicated that adolescents display similar patterns of cytokine expression after acute ethanol challenge, though the effects were severely blunted relative to young adults in most structures (Doremus-Fitzwater et al, 2015).…”
Section: Introductionmentioning
confidence: 87%
“…The floor of assay sensitivity using the Analox is ~12–15 mg/dl, as evidenced by background BEC measurements obtained from rats never exposed to ethanol. As such, measurements at or below those observed in vehicle-injected rats should be interpreted as zero values (Gano et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were run in triplicate in a 384-well plate (BioRad Laboratories) using the BioRad CFX 384 Real Time System C1000 Thermal Cycler (BioRad Laboratories). Relative gene expression was quantified using the 2−ΔΔCT method [41], with target gene expression calculated relative to the reference gene, β-actin (see [42] for primer sequences). Before analyses of target genes, reference gene expression was first separately analyzed in each structure/tissue compartment to ensure stability across treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…Interleukin-1β, IL-6, and TNF-α were measured, as these three cytokines have been shown to be potently activated in brain in response to systemic infection (e.g., [43]), with other non-immune challenges such as stress (e.g., [44, 45]) or ethanol exposure (e.g., [42, 46]) also altering central expression of these targets. Additionally, expression of nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα) was also assessed, as this is considered a reporter of nuclear factor kappa-light-chain-enhancer of activated B cells (NK-κB) activation.…”
Section: Methodsmentioning
confidence: 99%